Універсальний програмно-апаратний інтерфейс зв'язку з множиною вбудованих пристроїв - Гетьман, К. Р.; Шевцов, І. О. (ХНУРЕ, 2022)
The object of research is multiformat hub for embedded systems used in IoT (Internet of Things). The effective development of IoT is not only about the penetration of "connected" devices in all aspects of life, but also about the creation of a technological ecosystem, unified solutions for collecting, transmitting, aggregating data on a platform that allows processing data and using it to implement effective solutions. Availability of many inexpensive sensors and peripherals with different interfaces and communication protocols to work with IoT controllers. Standardized interfaces and communication protocols of most automation controllers impose restrictions on the use of many devices. At the same time, it is often not possible to use interface converters to connect an unsupported device to the automation controller.
Keywords: мікроконтролер; вбудовані пристрої